Pemanfaatan Inovasi Burung Hantu (Tyto Alba) sebagai Pengendali Hama Tikus (Rattus Argentiventer) oleh Anggota Subak di Desa Senganan Kecamatan Penebel KabupatenTabanan - ROHMAN, AZIZ FATHUR; SARJANA, I DEWA GEDE RAKA; ANGGRENI, IGAA LIES (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2020)
Utilizationof Owl Innovation (Tyto alba) as Rat Pests Controller (Rattus argentiventer) by Subak Members in Senganan Village, Penebel Sub-District, Tabanan Regency Rat pest control must be carried out in an integrated and sustainable way. One ofthe solution is to use owls because it does not create pollution and damage to rice plant. Pets controlusing an owl is determined by the knowledge and behavior of subak members. The purposes of this study is to determine the adoption process and the related factors in the use of owl as rat pets control of rets. The research locations was located in Senganan Village, Penebel Sub-District, Tabanan Regency using 35 respondents. The method used study is qualitative descriptive analysis andordinal measurement score. The result showed that level of knowing of respondents was in the high category with a score of 422. Pespondents’ persceptions were categorized as good with a score of 401. Pespondents’ behavior was categorized as very supportive with a score achievment of 451.Respondents’ attitudesupporting innovation was 91,43%, while thosewho were doubtful was 8,57%. The process of adopting subak members has arrived at the confirmation stage. In the confirmation stage, subak members support the sustainability of innovations applied in subak.Factors relatedto the use of innovation aresuperiority of innovation in the economy and social aspects of subak members, the suitability of innovation with the environment and the needs of subak members, and the ease of technical innovation. Although the number of rets in Senganan Village has decreased, subak members still need to preserve the existence of owl, especially in quarantine areas.